A model for achieving short-term and long-term goals in a leisure career. Issue 3 (2nd September 2017) - MacCosham, Bradley; Gravelle, François
Abstract : This article proposes a theoretical model for achieving short-term and long-term goals in a leisure career. A previous model illustrating the process between constraints, negotiation, motivation, and participation, as well as modifications made by other researchers, inspired the development of this model. The model illustrates how short-term negotiation strategies could be used to achieve short-term goals, which may also build up to the achievement of long-term goals, and how long-term negotiation strategies could be used to achieve long-term goals. The model is applied to the context of amateur athletes pursuing sport as a leisure career to demonstrate the progression through the stages of the model.